Proceedings of the 58th Annual Meeting of the Association for Computational Linguistics: System Demonstrations 2020
DOI: 10.18653/v1/2020.acl-demos.6
|View full text |Cite
|
Sign up to set email alerts
|

Personalized PageRank with Syntagmatic Information for Multilingual Word Sense Disambiguation

Abstract: Exploiting syntagmatic information is an encouraging research focus to be pursued in an effort to close the gap between knowledge-based and supervised Word Sense Disambiguation (WSD) performance. We follow this direction in our next-generation knowledge-based WSD system, SyntagRank, which we make available via a Web interface and a RESTful API. SyntagRank leverages the disambiguated pairs of cooccurring words included in SyntagNet, a lexical-semantic combination resource, to perform state-of-the-art knowledge-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
2

Relationship

3
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 26 publications
0
26
0
Order By: Relevance
“…Finally, we report results for knowledge-based systems (KB) that mainly rely on WordNet: Lesk ext +emb (Basile, Caputo, and Semeraro 2014), Babelfy (Moro, Raganato, and Navigli 2014), UKB (Agirre, López de Lacalle, and Soroa 2018), and TM (Chaplot and Salakhutdinov 2018). More recently, SyntagRank (Scozzafava et al 2020) showed best KB results by combining WordNet with the SyntagNet (Maru et al 2019) database of syntagmatic relations. However, as discussed in Section 3.2, we categorize these as knowledge-based because they do not directly incorporate sense-annotated instances as their source of knowledge.…”
Section: Comparisonmentioning
confidence: 99%
“…Finally, we report results for knowledge-based systems (KB) that mainly rely on WordNet: Lesk ext +emb (Basile, Caputo, and Semeraro 2014), Babelfy (Moro, Raganato, and Navigli 2014), UKB (Agirre, López de Lacalle, and Soroa 2018), and TM (Chaplot and Salakhutdinov 2018). More recently, SyntagRank (Scozzafava et al 2020) showed best KB results by combining WordNet with the SyntagNet (Maru et al 2019) database of syntagmatic relations. However, as discussed in Section 3.2, we categorize these as knowledge-based because they do not directly incorporate sense-annotated instances as their source of knowledge.…”
Section: Comparisonmentioning
confidence: 99%
“…SensEmBERT, which can, however, only disambiguate nouns; (ii) the best performing all-PoS system, i.e. SyntagRank (Scozzafava et al, 2020), a knowledge-based system; (iii) the feedforward baseline. We report results on the French, German, Italian and Spanish all-words evaluation datasets from SemEval-2013, which contain only nouns, and the Italian and Spanish datasets from SemEval-2015, which contain all PoS.…”
Section: Cross-lingual Wsdmentioning
confidence: 99%
“…The ability to identify the intended sense of a polysemous word in a given context is one of the fundamental problems in lexical semantics. It is usually addressed with two different kinds of approaches relying on either sense-annotated corpora (Bevilacqua and Navigli, 2020;Scarlini et al, 2020;Blevins and Zettlemoyer, 2020) or knowledge bases (Moro et al, 2014;Agirre et al, 2014;Scozzafava et al, 2020). Both are usually evaluated on dedicated benchmarks, including at least five WSD tasks in Senseval and SemEval series, from 2001 (Edmonds and Cotton, 2001) to 2015 (Moro and Navigli, 2015a) that are included in the Raganato et al (2017)'s test suite.…”
Section: Word Sense Disambiguationmentioning
confidence: 99%